Великий Шовковий шлях, якого не було - Хазанов, А.М. (Археологія і давня історія України, 2022)
У статті йдеться про формування, зміст та розуміння поняття «Великий Шовковий шлях». Автор доводить, що трансконтинентальної торгівлі шовком між Китаєм та країнами Близького Сходу і Європи в сучасному економічному розумінні у давнину не існувало. Торговельні зв’язки на так званій «трасі Великого Шовкового шляху» були спорадичними, нерегулярними та залежали від багатьох зовнішних чинників. Більш-менш стабільні торговельні операції між Китаєм та Заходом сформувалися лише у пізньому середньовіччі. Interregional long-distance trade in silk certainly existed in ancient and medieval times, but the transcontinental and regular «Great Silk Road», whether overland or even maritime, is a myth, a phantom. Its existence is not confirmed either by written sources or by archaeological data. A concept of the Silk Road implies at least knowledge of macro-routes and their final destination, as well as transcontinental connectivity. The latter, if it existed in antiquity and medieval times at all, was much more occasional than regular and intentional. As a rule, such trade involved many middlemen. The «Silk Road» and the trade in silk, even a trans-regional one, are quite different notions. The transcontinental overland trade existed in but a few short-lived historical periods; it was neither confined to silk nor was it even a road. The «silk roads» were only one of many long-distance continental and transcontinental trading itineraries that existed in the Old World in premodern times. It is also important to remember that transcontinental trade was limited only to high-value, low-volume goods. The exotic appeal of long-distance trade in luxuries combined with a striving for political correctness often results in distorted and exaggerated opinions on premodern commerce in general. Not only silk and other luxury and prestige goods, but also people, religions, languages, scientific knowledge, inventions, innovations, new technologies, know-how, chemicals, minerals, metals, plants, medicine, cultural transmissions and artistic styles and fashions, cuisine, and musical instruments moved along its numerous itineraries, but on the negative side, epidemic diseases and epizootics were also disseminated across Eurasia along with them. Finally, it is worth stressing again that the long-distance Eurasian trade not only directly or indirectly stimulated movements of people and created ethnic diasporas. Frequently it was just members of these diasporas who brought new knowledge and technological knowhow and contributed to their practical applications in the new milieus. That was the main achievement of Eurasian trade, with no continuity between the trade in silk in the ancient and medieval times.